Development of Accounting Practicum Learning Modules of Class XI Accounting Companies - Indayah, Indayah; Yoto, Yoto; Marsono, Marsono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The purpose of this research is designed to (1) Develop modules on the learning of the Accounting Practicum of class XI trading firms; (2) Know the feasibility of modules on the study of accounting practicum learning of trading companies based on validation of material experts, media experts, linguists and accounting learning practitioners; (3) Know the student's assessment of the accounting practicum learning module of a trading firm. This research is a research of development. The research design used refers to the Four-D (4D) model development model with four main stages, namely (1) Define, (2) Design, (3) Develop, (4) Disseminate. The data collection technique in this study is to use questionnaires and tests. The results of this study are (1) Development of modules by the Four-D models. Define obtained the result that students need modules that can improve students' competence, as well as help them learn independently. Design obtained the results of teaching materials that suit the needs of students in the form of accounting practicum modules of trading companies, Develop is validated by material experts, media experts, linguists and practitioners of accounting learning, revision according to expert advice and development trials in class XII Accounting, Disseminate, conducted module deployment in SMK Negeri 1 Boyolangu. (2) The eligibility of modules based on expert assessment of the material obtained score (decent), media expert obtained score (decent), Linguist obtained average score (decent), (3) Student assessment of module obtained very decent score.